2016
DOI: 10.1177/1934578x1601100605
|View full text |Cite
|
Sign up to set email alerts
|

New Antiplasmodial Diterpenes from Gutierrezia Sarothrae

Abstract: Bioassay guided fractionation of the MeOH extract of the plant Gutierrezia sarothrae (Asteraceae) using an assay for antiplasmodial activity against the drug-resistant Dd2 strain of Plasmodium falciparum led to the isolation of the two new diterpenes 3α-angeloyloxy-15-hydroxylabda-7,13-dien-16,15-olid-18-oic acid (1) and 3α-angeloyloxy-15-methoxylabda-7,13-dien-16,15-olid-18-oic acid (2). The structures of 1 and 2 were elucidated by interpretation of 1D and 2D NMR spectroscopic data, mass spectrometry, and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There have been previous investigations of the essential oil composition of G. sarothrae from New Mexico and from Utah, USA [35][36][37]. Diterpenoids, including polyalthic acid, daniellic acid, nivenolide, and gutierrezial [31][32][33], and flavonoids, including apigenin, luteolin, calycopterin, jaceidin, sudachitin, and sarothrin [34], have been isolated and characterized from G. sarothrae extracts. The plant is an invasive weed and there have been several reports on the toxic effects of livestock grazing on G. sarothrae, causing abortions [30].…”
Section: Introductionmentioning
confidence: 99%
“…There have been previous investigations of the essential oil composition of G. sarothrae from New Mexico and from Utah, USA [35][36][37]. Diterpenoids, including polyalthic acid, daniellic acid, nivenolide, and gutierrezial [31][32][33], and flavonoids, including apigenin, luteolin, calycopterin, jaceidin, sudachitin, and sarothrin [34], have been isolated and characterized from G. sarothrae extracts. The plant is an invasive weed and there have been several reports on the toxic effects of livestock grazing on G. sarothrae, causing abortions [30].…”
Section: Introductionmentioning
confidence: 99%
“…This plant was selected for study after its detanninized dichloromethane extract showed moderate antiplasmodial activity against the chloroquine-resistant Dd2 strain of P. falciparum . The Asteraceae family is a rich source of bioactive compounds, including antimalarial sesquiterpenes and diterpenes. However, there are no reports on the chemistry or antiplasmodial activity of P. pumila , so this extract was selected for investigation.…”
mentioning
confidence: 99%